The Twelver Shia in Modern Times : Religious Culture & Political History - Brunner, Rainer; Ende, Werner (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This volume - grown out of an international conference at Freiburg University in 1999 - deals with various aspects of Shiite Islam since the 18th century. It is divided into two major parts, the first of which is dedicated to traditional institutions of theology and learning and their transformation in modern times. The second part treats internal debates and the activities of Shiite dissidents, showing that Shiism is far from being uniform. Ideological and political developments in the 20th century and especially the Islamic Revolution in Iran have shaped the image of modern Shiism more than any other tendencies and are therefore also discussed in greater detail in Parts three and four. This book reflects the state of the art in this field of Islamic studies, its 21 contributions covering three centuries and a vast geographical range.